Ang paglilitis kay Dr. Jose P. Rizal = El proseso de Rizal - Peralejo, Cezar C. 4 0 16; 5 (Quezon City, Philippines : Sentro ng Wikang Filipino, 1999)
Narrates the court hearing, trial of Rizal.
In Tagalog.
Keywords: 2 -- 0; 6; Trials, litigation, etc. -- Rizal, Jose P. -- 1861-1896; 20; 2